Герой Задунайский: кончина, погребение и память о нем - Бекасова, А. (Науковi записки. Збiрник праць молодих вчених та аспiрантiв, 2009)
Статья посвящена рассмотрению процесса формирования героизированного образа полководца графа П.А. Румянцева-Задунайского в коллективной памяти конца XVIII – первой трети XIX вв. как одного из представителей российского имперского пантеона воинской славы. В статье анализируется техника социального воспоминания и производства значимого знания об историческом прошлом, а также процесс создания различных «мест памяти», связанных с именем графа Румянцева. Материалом для исследования послужили воспоминания о нем, оставленные современниками, разнообразные очерки биографического характера, портретные и скульптурные изображения, а также история создания и последующего бытования ряда учреждений мемориального характера, таких, например, как семейный музей. Стаття присвячена розгляду процесу формування героїзованого образу полководця графа П.О. Рум’янцева-Задунайського в колективній пам’яті кінца XVIII – першої третини XIX ст. як одного із представників російського імперського пантеону військової слави. В статті аналізується техніка соціального спогаду і виробництва значущого знання про історичне минуле, а також процес створення різноманітних «місць пам’яті», пов’язаних з ім’ям графа Рум’янцева. Матеріалом для дослідження слугували спогади про нього, залишені сучасниками, різноманітні нариси біографічного характеру, портретні та скульптурні зображення, а також історія створення та наступного побутування низки установ меморіального характеру, таких, наприклад, як сімейний музей. In the constellation of power during the reign of Catherine II count Petr Rumyantsev was not an ordinary figure. He was a talented army commander and became known after the successful siege of the Prussian fortress Kohlberg in the end of the 1750 s. It was his glorious victories over the Turks during the war of 1768–1774 that strengthened the Empress’ position on the Russian throne. Elevated to the rank of Marshal and rewarded with numerous estates and expensive gifts, he became one of the wealthiest and most decorated grandees of his time. Although he came to St.-Petersburg very rarely, he enjoyed wide popularity and influence at the imperial court. Rumiantsev was one of the great proconsuls of Catherine’s II rein whose duty was to incorporate Western frontier into the Russian Empire. His more than 20 year long tenure as a governor-general of the Ukraine offers one of the best examples of the governor general as a “broker” between St.-Petersburg and a peripheral region.